Fasciocutaneous Flap-A Versatile Technique to Resurface Leg and Foot - Collin Roy; Bijoy Majumdar; Siti Roy Chowdhury (Indian Journal of Plastic Surgery)
A total of fourteen cases of full thickness defects of leg and foot have been resurfaced with fasciocutaneous flaps either as a local rotation-transposition or island flap in a single-staged procedure. All the flaps were proximally based and were found to be vascular and reliable. The results were satisfactory functionally amd cosmetically with acceptable donor site morbidity.